MECHANISMS OF MANAGEMENT OF ORGANIZATIONAL INTERACTION OF AGRICULTURAL SYSTEM ENTERPRISES - FURMAN, IRINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
A study of the structure of the economic mechanism of management. The mechanism of functioning of agro-industrial integration is determined. In group form, the complex action of this mechanism should be aimed at: optimizing the structure of agro-industrial complex, including all industries and production, increasing the efficiency of agricultural production from the concentration of economic entities, creating favorable conditions for small businesses in agriculture on the basis of horizontal and vertical integration, determination of scales and capacities of large integrated associations for agro-industrial complex of Ukraine, balance of territorial structure of agro-industrial complex by forms of management, assessment of dynamics of innovation and investment activity of large corporate structures, support of economic entities in their desire to integrate with powerful producers. integration activities in the agro-industrial complex. A conceptual model for improving the mechanisms of economic regulation of reproduction proportions in the agro-industrial complex has been developed. It is determined that the modeling of the organizational and economic mechanism should include: algorithm for creating an integrated structure, which determines the legal form, authorized capital, form of agricultural land use (lease or transfer to authorized capital), ownership of manufactured products, material and technical resources and land, formation of the program of economic activity with definition of principles of their formation and subjects of planning, conditions of financing of current activity and investment in production development, definition of type of management, conditions of payment and material stimulation, distribution of the received income on final product, formation of social conditions of development rural areas. It is substantiated that the implementation of the developed content of the mechanism in management allows to: achieve a competitive state in the food market and ensure sustainable growth of all members of the integrated association, to form a common interest of agro-industrial association members in the final results of joint activities. obligations of all participants in the formation, to adhere to the equivalence of product exchange and profit distribution depending on the participation of each business entity in the integrated structure, to ensure the balance and proportionality of the production and material base.
Keywords: mechanism; management; organization; interaction; agro - industrial complex; structure; modeling; integration; enterprise; economic activity; financing